Chronic orbital inflammatory disease: parasitisation of orbital leucocytes by mollicute-like organisms. Issue 11 (November 1989) - Wirostko, E; Johnson, L; Wirostko, B
Abstract : Chronic orbital inflammatory disease (COID) is usually considered non-infectious and idiopathic. Treatment is empirical, palliative, and may not prevent disease progression. COID occurs in isolation or in association with various systemic diseases. Exophthalmos may be an important presenting sign. Vasculitis, lymphoid infiltrates, and granulomas are common. Mollicute-like organisms (MLO) parasitising and destroying vitreous leucocytes are often found to cause human chronic uveitis when an appropriate search is made. Inoculation of these MLO into mouse eyelids produced chronic uveitis and exophthalmic orbital inflammatory disease. Mollicutes are cell wall deficient bacteria. Extracellular mollicutes cause human and animal diseases characterised by lymphoid infiltrates, immunosuppression, and autoantibody production. Intracellular morphologically similar bacteria are non-cultivable pathogens termed MLO. Identification is based on direct detection in diseased cells by transmission electron microscopy. MLO are cytopathogenic and detection is aided by the alterations they produce. MLO replace the cytoplasm, destroy the organelles, and alter the nucleus. This results in cell proliferation, destruction, and dysfunction. MLO parasitise lymphocytes, monocytes, and polymorphonuclear leucocytes. This report describes orbital leucocytes parasitised by MLO in three patients with isolated COID. Rifampicin treatment of MLO disease is discussed.